A home-based, post-discharge early intervention program promotes motor development and physical growth in the early preterm infants: a prospective, randomized controlled trial - Juan Fan; Jianhui Wang; Xianhong Zhang; Ruiyun He; Shasha He; Mei Yang; Yujie Shen; Xiaojun Tao; Mei Zhou; Xiong Gao; Lijun Hu (BMC, 2021)
Abstract Background The implementation of early intervention (EI) in medical settings is time-consuming and resource-intensive, which limits its extensive use. In 2018, the Chinese Eugenics Association developed a home-based, post-discharge EI program. This study aims at evaluating the impact of this EI program on neurodevelopment and physical growth of early preterm infants. Methods This study was a prospective, partially blinded, randomized controlled trial (RCT), followed by an open phase. A total of 73 infants born at 28+ 0 ~ 31+ 6 weeks' gestation who were admitted to the Children's Hospital of Chongqing Medical University between December 1, 2019, and June 31, 2020, were enrolled. Another 33 infants were retrospectively recruited as the reference group. Thirty-seven infants randomized in the first early intervention, then standard care (EI-SC) group performed a 30-day EI during RCT period, while 36 infants allocated to SC-EI group were given EI in the following open phase. The test of infant motor performance (TIMP), development quotient (DQ), and anthropometric measures (length, weight, head circumference) were measured at the baseline (T0), termination of the RCT (T1), and termination of the open phase (T2). Repeated measures analysis was performed for comparison among groups. Results From T0 to T1, both groups had significant improvements in all outcome measures (all p < 0.001). A 30-day EI program was more effective in improving TIMP than standard care (from 53.12 ± 8.79 to 83.50 ± 11.85 in EI-SC group vs from 50.52 ± 8.64 to 75.97 ± 13.44 in SC-EI group, F = 4.232, p = 0.044). EI-SC group also had greater improvements in length, weight, and head circumference than SC-EI group (all p < 0.05). From T0 to T2, there was no significant difference regarding the improvements in all outcomes between the groups (all p > 0.05). At the endpoint of T2, the EI-SC and SC-EI group had similar TIMP and anthropometric measures, but much higher than the reference group (all p < 0.05). Conclusions These findings demonstrated that a home-based, post-discharge EI program in this study was a practical approach to promote motor development and physical growth in early preterm infants. Trial registration CHICTR, CTR1900028330, registered December 19, 2019, https:// http://www.chictr.org.cn/showproj.aspx?proj=45706